PENGARUH FASILITAS DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO SEMBAKO BAROKAH MLANDINGAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Budi, Fahrurrozi Oktavian Setia; Soeliha, Siti; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of facilities and brandimage on purchasing decisions at the Barokah Mlandingan Grocery Store withConsumer Satisfaction as an Intervening Variable. The sampling technique usedin this study was simple random sampling with the Slovin formula with a tolerableerror rate of 10% as many as 95 people. Data analysis and hypothesis testing inthis study used the Structural Equation Model - Partial Least Square (PLS-SEM)The results of the direct influence hypothesis test using the Smart PLS 3.0application, indicate that facilities have a positive and significant effect onconsumer satisfaction, brand image has a positive and significant effect onconsumer satisfaction, facilities have a positive and significant effect onpurchasing decisions, brand image has a negative and insignificant effect ondecisions purchase, consumer satisfaction has a positive and significant effect onpurchasing decisions, facilities have a positive but not significant effect onpurchasing decisions through consumer satisfaction, brand image has a positiveand significant effect on purchasing decisions through consumer satisfaction.